2019
DOI: 10.3389/fneur.2019.00837
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Motor Imagery for Grasping Actions in Children With Spastic Unilateral Cerebral Palsy

Abstract: Background: Motor Imagery (MI) refers to mental simulation of a motor action without producing any overt movement. Previous studies showed that children with Unilateral Cerebral Palsy (UCP) are impaired in implicit MI, as demonstrated by the performance of Hand Laterality Judgment tasks. The aim of this study was to examine the specificity of explicit MI deficits in UCP children. Methods: A group of UCP children ( n = 10; aged 9–14) performed a mental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…The development of MI ability has been extensively studied in children without impairments [ 42 , 50 ]. More recently, a few studies on MI ability in children with motor deficits such as development coordination disorder (DCD) [ 51 , 52 , 53 ] or cerebral palsy (CP) have been conducted [ 54 ]. DCD is a neurodevelopmental condition that is characterized by the inability to acquire and execute well-coordinated movements at an age-appropriate level [ 55 ], reflected by slow, effortful, inaccurate and ill-coordinated movements [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of MI ability has been extensively studied in children without impairments [ 42 , 50 ]. More recently, a few studies on MI ability in children with motor deficits such as development coordination disorder (DCD) [ 51 , 52 , 53 ] or cerebral palsy (CP) have been conducted [ 54 ]. DCD is a neurodevelopmental condition that is characterized by the inability to acquire and execute well-coordinated movements at an age-appropriate level [ 55 ], reflected by slow, effortful, inaccurate and ill-coordinated movements [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, their capability to retrieve motor representations should equally be preserved. Furthermore, they suggested that the application of explicit MI training could support the development of upper limb manipulation function in the cerebral palsy rehabilitation of children [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies addressing how to overcome such issues have suggested that MI training for children with CP should be performed with explicit (rather than implicit) MI [14]. Notwithstanding, even explicit MI capability can be affected by brain lesions [15] and, hence, the patients' neuropathophysiology must be considered for MI-based neurorehabilitation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Most children with perinatal stroke manifest major differences in the developmental organization of their motor system, often engaging major components of the motor system in the non-lesioned hemisphere (Alawieh et al, 2017;Craig et al, 2018Craig et al, , 2019. How this disrupted developmental plasticity impacts motor imagery systems is poorly understood though abnormalities in more generic CP populations are described (Errante et al, 2019). Source localization analysis would be one approach that might enhance understanding of mechanisms underlying motor imagery in individual children.…”
Section: Discussionmentioning
confidence: 99%